2013
DOI: 10.1083/jcb2004oia8
|View full text |Cite
|
Sign up to set email alerts
|

Macroautophagy substrates are loaded onto MHC class II of medullary thymic epithelial cells for central tolerance

Abstract: Macroautophagy serves cellular housekeeping and metabolic functions through delivery of cytoplasmic constituents for lysosomal degradation. In addition, it may mediate the unconventional presentation of intracellular antigens to CD4 + T cells; however, the physiological relevance of this endogenous MHC class II loading pathway remains poorly defined. Here, we characterize the role of macroautophagy in thymic epithelial cells (TECs) for negative selection. Direct presentation for clonal deletion of MHC class II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 38 publications
4
32
0
4
Order By: Relevance
“…Additionally, in the absence of FAT10, increased percentages of OT-II CD4SP in the thymus were observed, suggesting a reduced negative selection in these mice. Autophagy in thymic epithelium is an essential process in mediating tolerance of CD4 + cells (36,37). It has been demonstrated that the autophagosomal receptor p62/SQSTM1 becomes covalently mono-FAT10ylated at several lysines and that FAT10 colocalizes with p62 in p62 bodies (19).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the absence of FAT10, increased percentages of OT-II CD4SP in the thymus were observed, suggesting a reduced negative selection in these mice. Autophagy in thymic epithelium is an essential process in mediating tolerance of CD4 + cells (36,37). It has been demonstrated that the autophagosomal receptor p62/SQSTM1 becomes covalently mono-FAT10ylated at several lysines and that FAT10 colocalizes with p62 in p62 bodies (19).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the class II pathway, once the mt peptides enter the cytosol, they could be recruited into the endosome pathway by autophagy, a well-established mechanism by which viral Ags enter the MHC class II pathway in infected cells (35)(36)(37). Autophagy is the major mechanism by which thymic epithelial cells present Ags, including soluble mt Ags in the class II pathway for negative selection (38)(39)(40). It would be expected that the immune system would be tolerant to normal mt peptides delivered to the class II molecule by autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Les résultats obtenus avec un modèle murin présentant une déficience conditionnelle en ATG7 dans l'épithélium thymique a conduit les auteurs à conclure que l'autophagie ne participait pas à l'édu-cation thymique. On peut cependant penser que dans ce modèle déficient en ATG7, une activité autophagique résiduelle permettrait l'éducation des LT. L'équipe de Klein a montré peu de temps après, grâce à un nouveau modèle de délétion conditionnelle, que l'autophagie des cellules épithéliales thymiques exprimant AIRE (autoimmune regulator) [19] (➜), participait à la sélection négative via la pré-sentation par le CMH de classe II [20]. Le rôle de l'autophagie du stroma thymique dans l'éduca-tion des LT semble conforté par une étude récente.…”
Section: Autophagie Et éDucation Des Lymphocytes Tunclassified
“…Les cellules épithé-liales thymiques (TEC) présentent un niveau élevé d'autophagie basale si on le compare à celui d'autres tissus. Cette activité autophagique permet la présentation de peptides du soi intracellulaires sur le CMH de classe II et intervient dans l'éducation des LT CD4 + [17,20,21]. Les LT déficients en autophagie depuis le développement thymique maintiennent une quantité de mitochondries importante lors de leur passage de la zone centrale vers la zone périphérique, les sensibilisant à l'apoptose [10,12].…”
unclassified